Community-based eye health screening report in Malaysia: urban-rural referral comparison - Saiful Azlan Rosli; Ai-Hong, Chen (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study compared urban and rural referrals from a community-based eye health screening program named 'Jom Check Mata Malaysia (JCMM)'. The program was carried out in nine different states in Peninsular Malaysia—a total of 18 screening locations with a mix of urban and rural. Two mobile eye clinics were mobilised for community-based eye health screenings. This study involved 3,139 participants (1,158 and 1,981 participants from rural and urban, respectively). Visual complaints were collected via interviews using an ocular symptom checklist. The visual acuity was screened using a Snellen Chart. Ocular health screening, including anterior and posterior eye segments, was screened using slit-lamp bio-microscopy and fundus camera. Overall referrals were 2,139 (68%), 846 (27%) and 362 (12%) based on visual complaints, visual acuity and ocular health screening, respectively. Rural locations had significantly higher referral rates for visual complaint screening (χ2 = 422.53, p<0.05), visual acuity screening (χ2 = 20.20, p<0.05) as well as ocular health screening (χ2 = 64.70, p<0.05) compared to the urban locations. There was a consistent pattern of higher rural referrals for all types of vision screening. Information from our three-category screening analysis could help to design a vision screening for our rural and urban populations.